Bicuspid Aortic Valve: Morphology, Clinic, Diagnosis, Complications - Y. L. Trysvetava (Столичная издательская компания, 2021)
Bicuspid aortic valve refers to common (0.5-2% of the population) congenital heart defects that are asymptomatic throughout life, with valve dysfunction and/or aortopathy (pathia- from Greek pathos disease), manifested by expansion, aneurysm or dissection of the vessel. The pathogenesis of the formation of a bicuspid valve is unknown, a genetic component is noted, since the defect develops as sporadic, familial, in combination with other congenital heart defects and with hereditary connective tissue disorders. Morphogenetic studies suggest that different phenotypes of bicuspid aortic valve can be considered as etiologically different diseases, with valve dysfunction or valve dysfunction and aortopathy. Aortic lesion is characterized by phenotypic heterogeneity due to genetic or hemodynamic features. Researchers are discussing the relationship between the phenotype of the bicuspid aortic valve and aortopathy to predict the course of the disease and select the optimal surgical treatment technique. Diagnosis of heart disease is based on the results of an echocardiographic study, magnetic resonance imaging. Surgical treatment is performed for significant hemodynamic disturbances resulting from insufficiency or stenosis of the aortic valve, in cases of infective endocarditis, the risk of which is high, with aneurysm or aortic dissection.